The Political Economy of the Gifts on Tiktok - Cristina-Oana Cristea (Sociologie Românească)
TikTok is a social platform that has become a significant social phenomenon characterized by its complexity. It is a multifaceted object of study, allowing research on various topics such as security and surveillance, algorithms and addiction, and communication and online interactions. However, the practice of giving on TikTok remains under-researched by social sciences. Therefore, the main objective of this article is to understand the practice of giving to discover how it structures the economy of attention. The data obtained were generated through digital ethnography, which involved several qualitative research methods and techniques: participatory and non-participatory observation and conducting semi-structured interviews. Data analysis revealed that virtual gifts must be understood in their dual manifestation: they are the means by which the virtual self is both subjectified and objectified by the platform. First, they contribute to the construction of the influencers' self because they reflect the appreciation and attention received from users, thus enhancing their social reputation. Secondly, the platform monitors and calculates the gifts obtained by influencers to remunerate them, acting like a real bureaucracy that classifies and ranks users according to their actions. The research results suggest that the virtual gifts should be understood as a manifestation of the economy of attention, through which the work of influencers is rewarded based on the attention and dedication they gain from others. The work of the influencer is based on the monetization of the self, and its transformation into an object of free consumption within an economic system centered on the attention of others, a perishable resource that must be constantly attracted.